مسميات الجنة في القرآن الكريم (دراسة تحليلية): Names of Heaven in the Holy Quran - Muhammad Asim, masim (Al Manhal Research Journal, 2021)
To discourage negative instincts of human being, and to inculcate morality and decency in their behavior, the system of accountability has been introduced in every religion of the world. The Holy Quran by presenting a glamorous picture of paradise also motivates its readers to be virtuous and pious. Moreover, it warns the wrongdoers and transgressors about sinful activities by creating fear of Hell in their hearts.The variety in the names of paradise mentioned in the Holy Quran shows that there are seven stages of paradise based on hierarchy of pious people according to their rank in the eyes of Almighty Allah. This article studies different names and stages of paradise mentioned in the Quran which areجنة الفردوس ، جنة النعيم ،جنة عدن ، جنة المأوى ، جنة الخلد ، جنة دار السلام ، جنة دار اليقين/ دار القرار/ دارالجلال.